Identification of Essential Oil Components of Salvia cryptantha Montbret & Aucher ex Bentham, Growing Wild in Turkey - BINGOL, U.; COSGE, B.; IPEK, A.; GURBUZ, B.; GEVEN, F.G. (Asian Journal of Chemistry, 2010)
The essential oils obtained by hydrodistillation of the aerial parts (leaves and stems) and flowers of Salvia cryptantha Montbret & Aucher ex Bentham (Labiatae), an endemic species of Turkey, were analyzed by GC-MS. The contents of essential oil were obtained 1.44 % in aerial part and 0.4 % in flower. Thirteen components in aerial parts oil and 10 components in flower oil were identified, representing 97.89 and 97.33 %, respectively. 1,8-Cineole (30.38 and 36.28 %), valencene (24.34 and 26.53 %) and camphor (12.29 and 14.72 %) were found as the major components of both aerial parts and flower oils, respectively.